In Silico Designing, ADMET Screening, MM/GBSA Binding Free Energy of Some Novel 8-Amino Substituted Apigenin Derivatives as DPP-IV Inhibitors Targeting Type-II Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2022)
Diabetes has long been a major issue for the world's health. Drugs for hypoglycemia are now administered orally and intravenously, however they have several toxic and adverse consequences. Therefore, there is an increasing demand to find anti-diabetic medications that are more potent and secure. Since it was discovered that apigenin is an edible, plant-derived flavonoid with no toxicity, scientists have been quite concerned. Plants are rich sources of apigenin (API), a well-known insulin-secretagogue and insulin-mimetic substance. In cretin enhancers known as dipeptidyl peptidase-IV (DPP-IV) inhibitors are used to treat diabetes. It is necessary to produce new agents, ideally from natural sources, with less negative consequences due to their unpleasant side effects.The purpose of this in-silico design process was to create new 8-Amino substituted apigenin derivatives (RSMS 1–50) with DPP-IV inhibitory action. Using Schrodinger suit 2020-3, docking studies of molecules RSMS1–50 are carried out against DPP–IV (PDB id–6B1E).The Glide module, the QikProp module, and the Prime-MMGBSA module of the Schrodinger suit are used to execute the molecular docking research for the designed compounds RSMS1–50. Based on the GLIDE score, the binding affinity of the proposed molecules RSMS 1–50 towards DPP–IV was selected. Many substances demonstrated effective hydrogen bonding and hydrophobic communication to obstruct DPP-IV enzyme. Comparing the compounds RSMS1-50 to conventional Vildagliptin (- 5.3) and Sitagliptin (- 5.6), they show significant Glide scores between - 4.32 and - 8.39. The proposed information concerning drug similarity includes the in-silico ADMET characteristics. The most potent inhibitor has positive MM-GBSA binding. The findings demonstrate that 8-Amino substituted apigenin derivatives should be taken into account as possible DPP-IV inhibitors. Further in vitro and in vivo studies may demonstrate the therapeutic potential of the substances, RSMS 10, 15, 35, 26, 30, 45, and 47 with substantial Glide scores.